The challenge of integrating offshore wind power in the U.S. electric grid. Part II: Simulation of electricity market operations. (April 2017) - Simão, H.P.; Powell, W.B.; Archer, C.L.; Kempton, W.
Abstract: The purpose of this two-part study is to analyze large penetrations of offshore wind power into a large electric grid, using the case of the grid operated by PJM Interconnection in the northeastern U.S. Part I of the study introduces the wind forecast error model and Part II, this paper, describes Smart-ISO, a simulator of PJM's planning process for generator scheduling, including day-ahead and intermediate-term commitments to energy generators and real-time economic dispatch. Results show that, except in summer, an unconstrained transmission grid can meet the load at five build-out levels spanning 7–70 GW of capacity, with the addition of at most 1–8 GW of reserves. In the summer, the combination of high load and variable winds is challenging. The simulated grid can handle up through build-out level 3 (36 GW of offshore wind capacity), with 8 GW of reserves and without any generation shortage. For comparison, when Smart-ISO is run with perfect forecasts, all five build-out levels, up to 70 GW of wind, can be integrated in all seasons with at most 3 GW of reserves. This reinforces the importance of accurate wind forecasts. At build-out level 3, energy from wind would satisfy between 11 and 20% of the demand for electricity and settlement prices could be reduced by up to 24%, though in the summer peak they could actually increase by up to 6%. CO2 emissions are reduced by 19–40%, SO2 emissions by 21–43%, and NOx emissions by 13–37%. This study finds that integrating up to 36 GW of offshore wind is feasible in the PJM grid with today's generation fleet and planning policies, with the addition of 8 GW of reserves. Above that, PJM would require additional investments in fast-ramping gas turbines, storage for smoothing fast-ramping events, and/or other strategies such as demand response. Highlights: Smart-ISO, a simulator of the PJM planning process, is developed, tested, and evaluated. Injecting large amounts of offshore wind power in the electric grid is feasible with today's planning and forecast methods. With large amounts of offshore wind power, electricity costs and emissions of CO2, SO2, and NOx are reduced significantly. Improvements in wind forecasts allow for integration of up to twice as much offshore wind power with half of the reserves.